Tailored calix[4]arene-gold nanoconjugate as a ultra-sensitive immunosensing nanolabel. - Verma, Nidhi; Sutariya, Pinkesh; Patel, Tvarit; Shukla, Malvika; Pandya, Alok (Biomedical Microdevices, 2023)
The construction of highly sensitive and specific immunosensing nanolabels have attracted tremendous attention in the development of reliable point-of-care disease diagnostics. However, there are still challenges with traditional immunoassays, such as complicated and time-consuming procedure, the use of enzyme label, non-specificity, and require readers for detection. Therefore, we have designed and developed site-directed antibody-immobilized calix[4]arene-gold nanoconjugate based colorimetric immunosensing nanolabel to offer high sensitivity. The prepared nanolabel enabled oriented binding of the antibodies by providing full accessibility of Fab domain for antigen binding. The improved sensitivity of the developed nanolabel was evaluated using vertical flow immunoassay (VFIA) for detecting C-reactive protein (CRP) with a lower detection limit up to 1 ng/ml. Our developed nanolabel was found to be highly specific, easy, quick, and appropriate for onsite detection. The nanolabel is validated with spiked blood samples which exhibited ~90% recovery having a relative error of ~2%. Furthermore, the nanolabel was also used for screening of human blood real samples which showed relative error of ~0.6%. The developed nanolabel can be utilized as a potential nanolabel for the quantitative detection of various biomolecules in clinical samples.